The Phenomenon of Intonation and Its Moral Role in Directing the Meaning - Selected Models from the Holy Qur’an [In Arabic] - Bouzennacha, Noureddine (Milev Journal of Research and Studies, 2023)
The Arabic language is characterized by a number of phenological phenomena that affect meaning; It directs the operative signification; Judging from those accompanying audio smears; This includes the phenomenon of intonation that affects the operative; You give it a meaning; It is not part of the installation or its structure; but to cover it; It performs a function (phenological, grammatical and semantic); Hence, this article aims to clarify the moral role of intonation in directing the significance; I have tried to answer the following main question: What is the moral role of intonation? In order to answer it; I followed the following steps: I started with an introduction; Then define the concept of toning; explaining its divisions; Then show examples; With results stated. Among the results: intonation contributes to the stereotyping of sentences, and directing the meaning of the operative